Towards preparedness for dam failure: An evidence base for risk communication for downstream communities. (November 2020) - Mehta, Amisha M.; Weeks, Clinton S.; Tyquin, Ellen
Abstract: Community evacuations following dam failures like that of Edenville and Sanford Dams in 2020 and the Oroville Dam in 2017 in the United States, and Toddbrook Reservoir Dam in the United Kingdom in 2019, highlight the importance of risk communication that is designed to educate and encourage safe community response. However, research on community knowledge of and response to dam failure is scarce, limiting evidence-based design of risk communication. To support the development of effective dam failure risk communication, in the current study we conducted in-depth exploratory interviews with 26 public participants and five national dam experts in Australia. The findings from this study identify areas of convergence and divergence between expert and public participants' perceptions of and knowledge about dam failure and risk mitigation strategies as well as responses to an existing risk communication message. This evidence base can serve to drive risk communication strategy and design that supports community knowledge of potential dam failure and improve preparedness.